2015
DOI: 10.3109/0886022x.2014.996730
|View full text |Cite
|
Sign up to set email alerts
|

Association between visit-to-visit clinic blood pressure variability and home blood pressure variability in patients with chronic kidney disease

Abstract: Although both clinic blood pressure (BP) variability and home BP variability are associated with the risk of cardiovascular disease, the relationship between both BP variabilities remain unclear. We evaluated the association between visit-to-visit variability of clinic BP (VVV) and day-by-day home BP variability (HBPV) in patients with chronic kidney disease (CKD). We recruited 143 CKD patients in whom we performed HBP measurements every morning and evening over seven consecutive days. We obtained clinic BP da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
(70 reference statements)
0
3
0
1
Order By: Relevance
“…The other limitation of the present study is the absence of antihypertensive prescription fill data and information regarding patients' adherence to treatment regimens. However, low antihypertensive medication adherence explained only a small proportion of BP visit-to-visit variability [38], which implied that the absence of medication adherence data does not have a major impact on the results of the present study.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The other limitation of the present study is the absence of antihypertensive prescription fill data and information regarding patients' adherence to treatment regimens. However, low antihypertensive medication adherence explained only a small proportion of BP visit-to-visit variability [38], which implied that the absence of medication adherence data does not have a major impact on the results of the present study.…”
Section: Discussionmentioning
confidence: 94%
“…However, recent studies have shown that long-term visit-to-visit variability of BP may have greater prognostic value than mean BP or short-term variability [19, 37, 38]. These studies recommended that optimal antihypertension treatment included avoidance of inconsistent BP control and large BP visit-to-visit variability [36].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in diabetic patients, both mortality [12,13] and cardiovascular diseases [12][13][14][15] have been associated with VVV also. Similarly, in patients after a first event of coronary heart disease [16,17], stroke [18,19], or acute heart failure [20], the higher the VVV the higher is the risk for a second event or hospitalization. Similarly, high VVV of BP was associated with endothelial damage [21], increased arterial stiffness [22], progression of coronary artery calcification [23], and left ventricular diastolic dysfunction [24], all of which may contribute to risk of death and cardiovascular outcomes.…”
mentioning
confidence: 98%
“…Αποτελέσματα συσχέτισης της VVV με την θνητότητα 268,269 και τα καρδιαγγειακά συμβάματα [268][269][270][271] είχαμε και από μελέτες σε διαβητικούς ασθενείς. Σε ασθενείς μετά από ένα συμβάν οξέος στεφανιαίου συνδρόμου 272,273 , αγγειακού εγκεφαλικού επεισοδίου 274,275 , ή οξείας καρδιακής ανεπάρκειας 276…”
Section: η μακροπρόθεσμη μεταβλητότητα σε ασθενείς με χννunclassified